Probiotic Potential and Safety Evaluation of Enterococcus faecalis OB14 and OB15, Isolated From Traditional Tunisian Testouri Cheese and Rigouta, Using Physiological and Genomic Analysis - Baccouri, Olfa (Front Microbiol, 2019)
Lactic acid bacteria (LAB) strains OB14 and OB15 were isolated from traditional Tunisian fermented dairy products, Testouri cheese and Rigouta, respectively. They were identified as Enterococcus faecalis by the MALDI TOF-MS (matrix assisted laser desorption-ionization time of flight mass spectrometry) biotyper system and molecular assays (species-specific PCR). These new isolates were evaluated for probiotic properties, compared to E. faecalis Symbioflor 1 clone DSM 16431, as reference. The bacteria were found to be tolerant to the harsh conditions of the gastrointestinal tract (acidity and bile salt). They were low to moderate biofilm producers, can adhere to Caco-2/TC7 intestinal cells and strengthen the intestinal barrier through the increase of the transepithelial electrical resistance (TER). Susceptibility to ampicillin, vancomycin, gentamicin and erythromycin has been tested using the broth microdilutions method. The results demonstrated that E. faecalis OB14 and OB15 were sensitive to the clinically important ampicillin (MIC = 1 μg/mL) and vancomycin (MIC = 2 μg/mL) antibiotics. However, Whole Genome Sequencing (WGS) showed the presence of tetracycline resistance and cytolysin genes in E. faecalis OB14, and this led to high mortality of Galleria Mellonella larvae in the virulence test. Hierarchical cluster analysis by MALDI TOF-MS biotyper showed that E. faecalis OB15 was closely related to the E. faecalis Symbioflor 1 probiotic strain than to OB14, and this has been confirmed by WGS using the average nucleotide identity (ANI) and Genome-to-Genome Hybridization similarity methods. According to these results, E. faecalis OB15 seems to be reliable for future development as probiotic, in food or feed industry.